2016
DOI: 10.11646/zootaxa.4200.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Electric organ discharges of South African Marcusenius species (Teleostei: Mormyridae) and their effectiveness as indicators of local species diversity

Abstract: Recent morphological and genetic studies have revealed two new species of snoutfish in South Africa, Marcusenius caudisquamatus and M. krameri, which had been confused with M. pongolensis, the South African bulldog fish. All known mormyriform fish are nocturnal and emit electric organ discharges (EODs) for communication that are characteristic for their species. This paper examines whether or not the EODs of these three closely-related South African species can be differentiated from each other. An EOD pulse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
2
Order By: Relevance
“…Myers 1960 (Kramer & van der Bank, 2011), Marcusenius (Kramer, 2013a;Kramer et al, 2007Kramer et al, , 2016aKramer et al, , 2016bKramer & Wink, 2013),…”
Section: Ecologyunclassified
See 1 more Smart Citation
“…Myers 1960 (Kramer & van der Bank, 2011), Marcusenius (Kramer, 2013a;Kramer et al, 2007Kramer et al, , 2016aKramer et al, , 2016bKramer & Wink, 2013),…”
Section: Ecologyunclassified
“…e.g. Campylomormyrus (Feulner et al ., ; Feulner et al ., ; Lamanna et al ., ), Cyphomyrus Myers 1960 (Kramer & van der Bank, ), Marcusenius (Kramer, ; Kramer et al ., , , ; Kramer & Wink, ), Mormyrops (Kramer, ), Mormyrus (Kramer, ; Moritz, ), Paramormyrops (Arnegard et al ., , , ; Arnegard & Hopkins, ; Gallant et al ., ; Rich et al ., ; Sullivan et al ., ), Petrocephalus (Kramer et al ., ; Lavoué et al ., , ; Lavoué & Sullivan, ; Moritz et al ., ), Pollimyrus (Kramer et al ., ; Markowski et al ., ) and Stomatorhinus Boulenger 1898 (Sullivan & Hopkins, ).…”
Section: Signal Evolution and Sensory Ecology In Mormyroid And Gymnotunclassified
“…Southern Africa was previously assumed to have low diversity of mormyrid fishes, with only nine recognized species, which were all considered to have broad distribution ranges (Skelton, 2001). Nonetheless, over the past two decades, several integrative taxonomic studies in the region have shown that most mormyrid genera contain a number of species that were previously unknown to science (Kramer, 2013; Kramer et al ., 2003; Kramer et al ., 2004; Kramer et al ., 2007; Kramer et al ., 2012; Kramer et al ., 2016; Kramer & Swartz, 2010; Kramer & van der Bank, 2000; Kramer & van der Bank, 2011; Kramer & Wink, 2013; Maake et al ., 2014). These studies have led to the description of 17 new species and the resurrection of 1 species, indicating that mormyrid diversity in southern Africa remains underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…studies in the region have shown that most mormyrid genera contain a number of species that were previously unknown to science (Kramer, 2013;Kramer et al, 2003;Kramer et al, 2004;Kramer et al, 2007;Kramer et al, 2012;Kramer et al, 2016;Kramer & Swartz, 2010;Kramer & van der Bank, 2000;Kramer & van der Bank, 2011;Kramer & Wink, 2013;Maake et al, 2014). These studies have led to the description of 17 new species and the resurrection of 1 species, indicating that mormyrid diversity in southern Africa remains underestimated.…”
mentioning
confidence: 99%